Neuroimaging and clinicopathological differences between tumefactive demyelinating lesions and sentinel lesions of primary central nervous system lymphoma - Sun, Chenjing; Han, Jinming; Lin, Ye; Qi, Xiaokun; Li, Changqing; Liu, Jianguo; Qiu, Feng (Frontiers in Immunology, 2022)
Objective It is still a challenge to distinguish sentinel lesions of primary central nervous system lymphoma (PCNSL) from atypical tumefactive demyelinating lesions (TDLs) in clinical practice. We aimed to investigate potential differences of clinical features, neuroimaging findings and pathological characteristics between PCNSL and TDLs, improving early accurate diagnosis. Methods It was a retrospective study involving 116 patients with TDLs and 150 patients with PCNSLs. All cases were pathologically confirmed. Clinical features, neuroimaging findings and pathological characteristics between two groups were analyzed. Results The onset age was 37 ± 14 years in TDLs and 58 ± 13 years in PCNSL(p=0.000). Main onset symptom was headache in TDLs, while cognitive impairment was frequently noted in PCNSL. CT brain scan image showed hypodense lesions in most cases of TDL (110/116, 94.8%), while approximately 80% patients (120/150) with PCNSL had hyperdense lesions. Furthermore, we found that the presence of Creutzfeldt-Peters cells (might be misdiagnosed as tumor cells) may serve as an important feature in TDLs. Conclusions Onset age of patients with TDLs was younger than PCNSL. Neuroimaging features on brain CT scan might provide clues to make a differential diagnosis. Pathological features of PCNSL with sentinel lesions or following steroids therapy might mimic TDLs. Dynamic neuroimaging pathological and follow-up information were essential for an accurate diagnosis.